Synthesis, anti-inflammatory activity, and molecular docking studies of some novel Mannich bases of the 1,3,4-oxadiazole-2(3H)-thione scaffold - Ozyazici, Tugce; Gurdal, Enise E.; Orak, Duygu; Sipahi, Hande; Ercetin, Tuba; Gulcan, Hayrettin O.; Koksal, Meric (Wiley-V C H Verlag Gmbh, 2020)
A series of novel ibuprofen and salicylic acid-based 3,5-disubstituted-1,3,4-oxadiazole-2(3H)-thione derivatives was synthesized, and they were evaluated as potential anti-inflammatory agents. Following the structure identification studies employing IR, H-1 nuclear magnetic resonance (NMR), C-13 NMR, and elemental analysis, the title compounds were tested by cyclooxygenase (COX)-1 and COX-2 inhibition assays concomitant to lipopolysaccharide (LPS)-induced nitric oxide and prostaglandin production prevention experiments. The results indicated that the majority of the compounds displayed either a superior or comparable activity in preventing both LPS-induced NO production and COX-1 activity in comparison to the activities of the reference molecules. Furthermore, docking studies were also performed to reveal possible interactions with the COX enzymes.
Keywords: 1; 3; 4-oxadiazole; anti-inflammatory activity; COX-1; COX-2; LPS-induced NO production; molecular docking study; PGE(2)